Nutritional Status and Infectious Disease of Undernourished Children under five in Desa Cipacing, Jatinangor Subdistrict, West Java, from April to December 2012 - Palomina Caesarea Nurhasanah; Dewi Marhaeni Diah Herawati; Resnaldi Resnaldi (Faculty of Medicine Universitas Padjadjaran, 2015)
Background: Undernutrition frequently occurs in children under five. If not treated, it will cause acute health effects and affect on cognitive development, social, physical work capacity and productivity. Undernutrition can be accompanied by the presence of infectious disease that can worsen the children’s nutritional status. This study aimed to describe the nutritional status and infectious disease of undernutrition children under five in Jatinangor Subdistrict.Methods: A qualitative study was carried out to 7 parents and undernourished children under five, in Desa Cipacing, Jatinangor. It was conducted from April to December 2012. The inclusion criterias were undernourished children under five with a history of infectious disease in the previous year, and the parents were willing to participate in this study. Exclusion criteria were parents and/or the children who were not at home when the collection of the data was conducted.. Data collection was conducted using measurement of nutritional status, in depth interview and environmental observation. The data were presented in tables, figures and narration.Results: Three subjects with undernutrition (-3SD to -2SD) and four subjects with severe undernutrition (<-3SD). Factors affecting poor nutritional status were weight loss, no significant weight gain, diet and eating habit, and onset of disease. Commonly occurred infectious diseases were common cold, diarrhea, fever and cough. Some factors affecting infectious diseases were family member transmission, immunization, and treatment behavior.Conclusions: Poor nutritional status and infectious diseases contribute to undernutrition in children under five. DOI: 10.15850/amj.v2n3.553